Digital Transformation in Nursing Practice: Leveraging Technology for Patient Education and Clinical Decision Support - Ani Susiani; Jummai Wennie; Masliha Masliha (Qualitative and Quantitative Research Center, 2025)
The digital transformation in healthcare has driven the emergence of nursing technologies as strategic innovations that bridge the gap between the limitations of conventional service methods and the demands of modern nursing care. However, the effectiveness of these technologies largely depends on how they are leveraged for patient education and clinical decision support to improve service quality. This study aims to analyze the impact of digital transformation in nursing practice with a focus on three key dimensions: technology utilization, patient education, and clinical decision support. A quantitative approach with a cross-sectional survey design was employed, involving 300 nursing participants from Indonesia and Nigeria selected through purposive sampling. Data were collected via an online questionnaire and analyzed using multiple linear regression. The findings reveal that technology utilization exerts a significant effect on the effectiveness of patient education, and patient education acts as a strong predictor of accurate clinical decision support. Furthermore, increased technology integration is consistently predicted to enhance nurses' decision-making capacity and quality of care, whereas technological barriers may potentially diminish both. In conclusion, digital transformation in nursing has demonstrated clear advantages over conventional methods in terms of information efficiency, education accessibility, and clinical decision accuracy. This study contributes by integrating patient education and clinical decision support into digital health adoption literature, while also offering practical guidance for system developers and policymakers to create more efficient and evidence-based nursing practice environments in developing countries.